2021
DOI: 10.1089/andro.2021.0016
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and Adult Neurogenesis in the Hippocampus

Abstract: Adult neurogenesis in the hippocampus is modulated by steroid hormones, including androgens, in male rodents. In this review, we summarize research showing that chronic exposure to androgens, such as testosterone and dihydrotestosterone, enhances the survival of new neurons in the dentate gyrus of male, but not female, rodents, via the androgen receptor. However, the neurogenesis promoting the effect of androgens in the dentate gyrus may be limited to younger adulthood as it is not evident in middle-aged male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 181 publications
(199 reference statements)
0
7
0
Order By: Relevance
“…The copyright holder for this preprint this version posted March 30, 2023. ; https://doi.org/10.1101/2023.03.29.534716 doi: bioRxiv preprint with letrozole, in line with prior results [19,34], induced an antidepressant-like effect exclusively in female rats, which parallel the increased in testosterone levels observed 1 h post-treatment. Remarkably, the repeated administration of testosterone was previously shown to induce an antidepressant-like response in the forced-swim test [37] and to increase hippocampal neurogenesis (see review by [38]), suggesting a role for this hormone in the beneficial effects induced by letrozole in female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted March 30, 2023. ; https://doi.org/10.1101/2023.03.29.534716 doi: bioRxiv preprint with letrozole, in line with prior results [19,34], induced an antidepressant-like effect exclusively in female rats, which parallel the increased in testosterone levels observed 1 h post-treatment. Remarkably, the repeated administration of testosterone was previously shown to induce an antidepressant-like response in the forced-swim test [37] and to increase hippocampal neurogenesis (see review by [38]), suggesting a role for this hormone in the beneficial effects induced by letrozole in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…One could speculate that letrozole could either be acting synergistically on the same molecular pathways targeted by ketamine or in additional molecular pathways, producing the enhanced physiological response observed. Moreover, and as discussed in the context of the beneficial effects of letrozole observed in females, it is possible that the increase in testosterone that accompanies aromatase inhibition might be responsible for the improved antidepressant-like response (i.e., [37][38]) induced by ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, when healthy adult mice were treated with antibiotics for 7 weeks, long-term neurogenesis in the SGZ of the DG was significantly impaired, but this change could be fully reversed through probiotic administration and voluntary exercise [276]. Moreover, an interesting study showed that C57BL/6 mice that received fecal microbiota transplantation from 5xFAD mice displayed decreased adult hippocampal neurogenesis and brain-derived neurotrophic factor expression and increased p21 expression, resulting in memory impairment and microglial activation [277]. Gut microbes can also regulate microglia and cognitive function during malnutrition and regulate enteric neurons and glia [183,278].…”
Section: Gut Microbiomementioning
confidence: 99%
“…Extensive research has focused on analyzing the role of sex steroids in determining sex differences in the hippocampus. In this brain region, a sex‐dependent regulation has been detected in cell proliferation and survival (Barker & Galea, 2008), number and density of dendrites (Mathias et al, 2010; Segarra & McEwen, 1991), patterns and density of fibers (Madeira & Paula‐Barbosa, 1993), and neurogenesis (Blankers & Galea, 2021; Duarte‐Guterman et al, 2015), among others. In addition, accumulating evidence indicates that the hippocampus is a key player in sex steroid synthesis (Brandt et al, 2020; Gall et al, 2023; Hojo et al, 2009).…”
Section: Brain Differences From the Sex Perspectivementioning
confidence: 99%